2011
DOI: 10.1182/blood-2010-06-288480
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of treatment strategies for patients with intestinal diffuse large B-cell lymphoma: surgical resection followed by chemotherapy versus chemotherapy alone

Abstract: The aim of this retrospective cohort study was to analyze the impact of surgery on the outcomes and qualities of life (QOL) in patients with intestinal diffuse large B-cell lymphoma (DLBCL). We assessed 345 patients with either localized or disseminated intestinal DLBCL and compared them according to treatment: surgical resection followed by chemotherapy versus chemotherapy alone. In patients with localized disease (Lugano stage I/II), surgery plus chemotherapy yielded a lower relapse rate (15.3%) than did che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
138
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(152 citation statements)
references
References 23 publications
12
138
0
2
Order By: Relevance
“…A recent Chinese study (n = 116) reported that in addition to female sex and B-cell phenotype, radical surgery was an independent prognostic factor for better OS, as determined by multivariate analysis [27]. Another large study from Korea on 345 patients with intestinal DLBCL revealed that among stage I/II 1 patients, those treated by surgery plus chemotherapy (CHOP or R-CHOP) showed significantly better survivals than those treated by chemotherapy alone [28]. In addition, multivariate analysis revealed that surgery plus chemotherapy was a sole independent prognostic factor for better OS [28].…”
Section: Treatment For Gastrointestinal Lymphomamentioning
confidence: 99%
“…A recent Chinese study (n = 116) reported that in addition to female sex and B-cell phenotype, radical surgery was an independent prognostic factor for better OS, as determined by multivariate analysis [27]. Another large study from Korea on 345 patients with intestinal DLBCL revealed that among stage I/II 1 patients, those treated by surgery plus chemotherapy (CHOP or R-CHOP) showed significantly better survivals than those treated by chemotherapy alone [28]. In addition, multivariate analysis revealed that surgery plus chemotherapy was a sole independent prognostic factor for better OS [28].…”
Section: Treatment For Gastrointestinal Lymphomamentioning
confidence: 99%
“…Among patients with localized diseases, the relapse rate was lower in patients receiving chemotherapy following surgical resection than in patients receiving chemotherapy alone. The survival rate of 3 years following treatment was also significantly high in patients receiving chemotherapy following surgical resection (p<0.001) (2). Surgical resection and CHOP chemotherapy were performed in patients diagnosed with localized DLBCL in the ileocecal region.…”
Section: Discussionmentioning
confidence: 99%
“…Among these cases, lymphomas with extra-nodal involvement may be seen. However, an increasing number of recent publications indicate that chemotherapy, added to surgical resection, in local mass lymphoma is more successful than chemotherapy alone (2). These rare cases may occasionally present with abdominal pain, abdominal mass, and acute abdomen.…”
Section: Introductionmentioning
confidence: 99%
“…Seokjinkim et all in 2011 concluded that combination of surgery and chemotherapy improves survival in localized disease. [4] Whereas Beaton C et al, in their study in 2012 haverecommended that chemotherapy be the principal mode of treatment and surgery be reserved for patients with clinical indication. [5] Our patient was treated with chemotherapy, and surgery was deferred since there was no evidence of obstruction.…”
Section: Diagnosismentioning
confidence: 99%